Pengaruh Kepemimpinan Transformasional, Budaya Kerja dan Pengalaman Kerja Terhadap Kinerja Karyawan PT.Natafari Bengkulu - Aji Fakhrizal Syahbet; Markoni Markoni; Fauzan Fauzan (Jurnal Mirai Management, 2023)
This study aims to determine how much influence transformational leadership (X1) work culture (X2) and work experience (X3) have on employee performance (Y) PT. Natafari Bengkulu. using the Likert scale method by distributing questionnaires to respondents. This study also aims to determine the effect of Transformational Leadership, Work Culture, and Work Experience partially and simultaneously on Employee Performance, and to determine which of the variables Transformational Leadership, Work Culture, and Work Experience have the most significant effect on Employee Performance. This study uses a quantitative approach, explanatory format and this type of research is survey research. The population in this study were all employees of PT. Natafari Bengkulu, 45 samples with saturated sample method. The analytical tool used in this research is multiple linear regression analysis, using SPSS version 25 for windows. The results of the study show that (1) Transformational leadership has a significant effect on the performance of employees at PT. Natafari Bengkulu, (2) Work Culture has a significant effect on the performance of employees of PT. Natafari Bengkulu, (3) Work Experience has a significant effect on the performance of employees of PT. Natafari Bengkulu, (4) Transformational leadership, work culture and work experience simultaneously influence the performance of employees of PT. Natafari Bengkulu. Keywords: Transformational Leadership, Work Culture, Work Experience, Employee Performance